China’s Holdings of U.S. Treasury Securities: Economic Investment or Strategic Tool in Bilateral Relations? - Yue Xu; Yu Kuang; Dayu Zhai; Danyang Zhao (SAGE Open)
As the second-largest holder of U.S. Treasuries, China’s investment behavior in U.S. debt has long sparked debate about whether economic factors or strategic considerations primarily drive it. Based on the “weaponized interdependence” theory, the paper uses the time-varying parameter regression (TVP-R) and vector autoregression (VAR) models to capture the influence of China-U.S. relations and economic factors on China’s holdings of U.S. Treasury securities. The results show that the scale of foreign exchange reserves and China-U.S. relations have a significant positive impact on China’s holdings. In contrast, the holdings are not sensitive to Treasury returns or the trade balance. The foreign exchange reserve scale has a far greater impact than the China-U.S. relationship. Dynamic analysis indicates that China-U.S. relations and China’s holding decision show a trend of “decoupling,” and there is no evidence to prove that China weaponized the creditor’s rights. China’s holdings of U.S. Treasuries should be mainly regarded as an economic behavior to preserve the value of foreign exchange reserves. In the future, the strategic competition between China and the U.S. may have only a limited impact on China’s holding behavior.